A STUDY ON PROBLEM SOLVING ABILITY AND ACHIEVEMENT IN PHYSICS OF HIGHER SECONDARY STUDENTS IN COIMBATORE DISTRICT - N, Sutha; J, Vanitha (International Journal of Research -GRANTHAALAYAH, 2017)
The competence of problem solving has an energetic role in students’ academic outcomes and their construction of the ideas. Keeping this in vision, the current research has been planned out to inspect the effect of problem solving ability and the achievement in physics of higher secondary students in Coimbatore district. This study is under taken with an understanding to examining the association with problem solving ability and achievement in physics of different higher secondary students with the volume of 326 as sample size. The result concluded from the study that there is no significant relationship between problem solving ability and achievement in physics of higher secondary school students.